EVALUATION OF BRAIN-BLOOD BARRIER PERMEABILITY FOR NEURON-SPECIFIC ENOLASE DURING PERINATAL HYPOXIC-ISCHEMIC LESION OF THE CNS - D. V. Blinov (Акушерство, гинекология и репродукция)
There is a non-diminishing interest in the assessment of the blood-brain barrier (BBB) resistance and prediction of the severity and outcomes of the perinatal hypoxic-ischemic lesion of the CNS using the analysis of concentration of neuron-specific proteins in biological fluids. This defines the objective of our study – to evaluate the dynamics of serum neuron- specific enolase (NSE) concentration over a 6-month period of life in infants with cerebral ischemia using patient stratification according to their gestational age. Materials and Methods. 49 infants with the perinatal hypoxicischemic lesion of the CNS and gestational age between 32 and 41 weeks have been examined. 28 healthy term babies comprised the control group. For comparison patients were divided into the following groups: based on the 1-minute Apgar score: 1-3 scores (group А, 1-3), 4-6 scores (group А, 4-6) and 7-9 scores (group А, 7-9); based on their gestational age (GA): GA of 32-33 weeks, GA of 34-36 weeks and GA of 37-40 weeks; babies with the intra-ventricular hemorrhages (IVH group) and periventricular leukomalacia (PVL). Serum NSE levels were measured quantitatively using the enzyme immunoassay (EIA). Results. A significant increase of serum NSE levels was found in groups А 1-3, А 4-6and А 7-9 one week postpartum as compared to the control group. Over the whole observation period serum NSE concentration showed strong correlation with the severity of perinatal hypoxic-ischemic lesion of the CNS which was reflected in the Apgar score. Both during postpartum week one and further on the serum NSE levels were significantlyhigher in group GA 32-33 as compared to groups GA 34-36 and GA 37-41, as well as the control group. Starting from postpartum week one, serum NSE levels in the PVL group were significantly lower than in the IVH group. There was a delayed increase of serum NSE levels at postpartum week 4. Conclusion. The results obtained confirm the ongoinglong-term abnormal BBB permeability for NSE after the perinatal hypoxic-ischemic lesion of the CNS which reflects the chronic course of a given pathology. These changes are more pronounced in babies of lower gestational age.